Affordable housing in Portugal and São Paulo Municipality: Comparison of space standards and socio-economic indicators - Branco Pedro, J. (2012)
This paper compares the space standards set for affordable housing in Portugal and in São Paulo Municipality (Brazil), and seeks explanations for differences in the socioeconomic context of each territory. The Controlled Cost Housing (CCH) in Portugal and the housing built within the program My Home My Life (MHML) in São Paulo Municipality are studied. Three research questions are addressed: Which program has more demanding space standards? Which social-economic conditions explain the differences in space standards? How different space standards influence the users’ satisfaction? To answer these questions, space standards, socio-economic indicators and the users’ satisfaction are compared. Space standards compared the number and type of rooms, the internal floor area of dwellings, the size of rooms, and the size of furniture and equipment. The study has shown that space standards set for CCH are more demanding than those set for MHML program. For instance, a CCH dwelling has almost two times the gross area of a MHML dwelling with the same number of rooms. The housing deficit, the low income of poor households and the option to sell highly subsidized affordable housing are reasons that justify the low space standards in São Paulo Municipality when compared to Portugal. Although affordable houses are substantially smaller in São Paulo Municipality, the satisfaction level of dwellers with the size of dwellings is higher. Therefore, a direct link between space standards and users’ satisfaction cannot be set. We conclude that different political options on how to provide housing to low income households directly influence the space standards set for dwellings.